1963
DOI: 10.1017/s0021859600013666
|View full text |Cite
|
Sign up to set email alerts
|

The use of faecal nitrogen as an index for estimating the consumption of herbage by grazing animals

Abstract: Data from thirty-five digestibility trials with sheep in metabolism cages were used to investigate statistically the relationships between organic matter intake (I), faecal organic matter output (F), and the nitrogen concentration in faecal organic matter (N).The data fell easily into groups due to botanical or seasonal differences in the feed. These groups of data were homogeneous and provided highly significant linear equations of the forms I = bF + cFN and I = a + cFN. When compared these groups of data som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

1969
1969
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 11 publications
1
13
0
1
Order By: Relevance
“…Arnold and Dudzinski (1963) reported that selective grazing was one of the causes of error in the prediction of feed intake based on fecal N index. These authors also observed a large between-animal variation in fecal N output and OMI by sheep in feeding trial indoors.…”
Section: Digestibility Coefficient (%)mentioning
confidence: 99%
“…Arnold and Dudzinski (1963) reported that selective grazing was one of the causes of error in the prediction of feed intake based on fecal N index. These authors also observed a large between-animal variation in fecal N output and OMI by sheep in feeding trial indoors.…”
Section: Digestibility Coefficient (%)mentioning
confidence: 99%
“…Grazing is a complex process that is still not well understood. Considerable attention has been given to examining the factors which might influence the intake of herbage by large herbivores, and early investigations by Arnold and Dudzinski (1963), Spedding et al. (1966) and Allden and Whittaker (1970) on temperate pastures suggested that herbage intake by ruminants could be defined as the product of the biting rate, bite mass and the time spent grazing.…”
Section: Introductionmentioning
confidence: 99%
“…Digestibility of grazed forages cannot be deter-It is generally agreed that faecal nitrogen, which mined directly and has to be estimated by in-is not solely of dietary origin (Virtanen, 1966; Van direct means (Lambourne & Reardon, 1963;Soest, 1967), is the best indicator available Greenhalgh & Corbett, 1960). A number of indi- (Arnold & Dudzinski, 1963;McManus, Arnold & cator substances, nitrogen (Raymond, 1954;Dudzinski, 1966;Streeter, 1969). Local regression Arnold & Dudzinski, 1963), chromogens (Reid et al relationships between intake and some function of 1950), lignin (Van Soest, 1965) and minerals faecal nitrogen need to be established.…”
Section: Introductionmentioning
confidence: 99%
“…A number of indi- (Arnold & Dudzinski, 1963;McManus, Arnold & cator substances, nitrogen (Raymond, 1954;Dudzinski, 1966;Streeter, 1969). Local regression Arnold & Dudzinski, 1963), chromogens (Reid et al relationships between intake and some function of 1950), lignin (Van Soest, 1965) and minerals faecal nitrogen need to be established. The con- (McManus, Dudzinski & Arnold, 1967) naturally centration of nitrogen appearing in the faeces occurring in ruminant faeces have been used to may be influenced by parasitism of the host predict feed digestibility and feed intake.…”
Section: Introductionmentioning
confidence: 99%